Nová média - nové styly? - Krčmová, Marie (Stylistyka, 2002)
The concept of functional styles has been the part of stylistic investigations in the Czech and Slavonic studies since the 1930s. The concept offunctional styles operates with given general functions of language to which the individual language features are being found. mostly at the levels of naming units or composition of the text. The new, revised edition of the textbook Stylistika souëasné éeštiny [Stylistics of Contemporary Czech] brings again into question what level of generalization is possible when describing the level of style in language and what viewpoint in general is acceptable, with regard to the present-day differentiation of texts. Besides, it is necessary to take style as a quality of the whole unit of communication into consideration and to loose the relationship style-stylistics-standard language. The increasing number of media of communication also plays a significant role. It results in opening borders among cultures and „national" styles, covering up differences between written and spoken utterances and devaluation of written and spoken word, enlargement of group of people who can create public texts of notional orientation, growing importance of style for the producers’ presentation and the decrease of the possibility to identiñ’ them by the appearance of the text, substitution of real communication for virtual and origin of multimedia communication. Using language in communication and effects of these influences are ambiguous. In scholarly discussions it is pointed out that most of the existing texts are ambiguous as far as their function is concerned and that under these circumstances there is a growing number of texts which are polyfunctional or ambiguous as to their function. However, it is not the concept itself, i.e. the concept offunctional stylistics with several functional styles, that should be doubted, but rather the way the concept is usually applied. It is necessa ry to regard this concept not as an absolutely valid information about reality, but as a tool that provides the possibility to categorize the manifold reality of communication into cer tain general categories, so that it would be possible to discuss it at the level of metalanguage. The other extreme, the maximum enlargement of the number of general styles and giving up the concept ofstylistic norms, is not suitable. because it denies the role of stylistics as a generalizing scholarly discipline. The innovations concerning the orientation of stylistics should not lead to enlargement ofthe number of styles, but deeper - to new inve stigations concerning their essence. At present it is just possible to prepare such approach by scholarly discussions. "This is also a reflection of the new situation of communication reinforced by the new media: a scholarly discourse as a permanent direct discourse.